PENGARUH GAME INTERAKTIF TERHADAP PENINGKATKAN PEMAHAMAN KONSEP MATEMATIS SISWA SMP - Riyan Cahya (De Fermat : Jurnal Pendidikan Matematika, 2019)
The study aims to determine the influence of application of interactive game-assisted kahoot applications can improve the understanding of the concept. The method used in Presearch is the research of aniexperiments With The kinds of Experimenoyang Usesthen test T. The results of the research that has been done are and can be concluded that there is a difference or influence of Kahoot application interactive games to improve the understanding of mathematical concepts, the application of a kahoot interactive game is better than learning by using conventional learning in improving the ability to understand the mathematical concepts in working on the problem with Use the app's interactive game from the work of the book.